Fictitious commodification and agrarian change: Indigenous peoples and land markets in Highland Ecuador. (11th June 2020) - Goodwin, Geoff
Abstract: Creating private property rights and establishing land markets were fundamental to the historical development of capitalism in the Global North and remain at the centre of capitalist development in the Global South. This article contributes to debates about these processes by analysing the relationship between land markets and indigenous peoples in Highland Ecuador. Building on Karl Polanyi's concept of fictitious commodities, it elaborates a new concept that makes an analytical distinction between the activation and development of land markets. The former refers to the occasional participation of actors in markets to secure land, whereas the latter relates to the establishment and expansion of markets that regulate the distribution and value of land through market prices. Focusing on indigenous land struggles in the late 20th century, this article shows that the activation of land markets created opportunities for indigenous peasants to secure land, whereas the development of land markets closed them down. Social and class differentiation among the highland indigenous population increased through this contradictory process. The article connects this historical analysis to recent developments in Ecuador to contribute to empirical and theoretical debates about contemporary land struggles and agrarian change elsewhere in the Global South.